The transatlantic alliance in the Age of Trump - Oztig, Lacin Idil (ROUTLEDGE JOURNALS, TAYLOR & FRANCIS LTD, 2020)
NATO has successfully adjusted itself in the political and security environment of the post-Cold war era through enlargement, focusing on conflict prevention, crisis management and peacekeeping. Currently, the most important challenge to NATO comes from within. Under businessman-turned-U.S. President Donald J. Trump who focuses his attention on 'making America great again', the issue of burden sharing has dominated NATO's agenda. President Trump has pressured European countries to increase their defense spending to meet the 2% of GDP defense spending objective of NATO. While the previous U.S. presidents also pressured European states with regard to burden sharing, President Trump's rhetoric differs from his predecessors by associating American commitment to the Alliance directly to the defense spending of NATO's European members. Importantly, this article shows that despite Trump's skepticism of NATO and his rhetorical pressure on its member states regarding the issue of burden sharing, there is no change in the American approach to NATO at the policy level.
Keywords: NATO; transatlantic alliance; defense spending; the U.S; European countries; LESSONS; FUTURE; POLICY; EUROPE; Government & Law